2003
DOI: 10.1080/1357151032000126229
|View full text |Cite
|
Sign up to set email alerts
|

UK direct investment in the United States: a mode of entry analysis

Abstract: This article investigates the reasons underlying the high propensity of UK firms to directly invest in the United States via acquisition and merger. Using a binomial logit model, this study analyses data from 142 firms in five industrial sectors over the period 1984-1994. Together, these sectors account for more than 80% of UK foreign direct investment (FDI) in the sample period. The results highlight the role of diversification in explaining this behaviour. In contrast, the relative lack of evidence to suppor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0

Year Published

2009
2009
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 8 publications
1
7
0
Order By: Relevance
“…This implies that domestic firms are cheaper to acquire by foreign firms. Previous studies (Froot and Stein, 1991; Nisbet et al , 2003) with similar results indicated that strong currency lessens the costs of transaction, and therefore, firm that has its country’s currency depreciated tends to be a target. Although the countries of this ASEAN region made effort in maintaining strong currencies against the US dollars, their exchange rates depreciated substantially following the current plunge in crude oil prices.…”
Section: Resultsmentioning
confidence: 69%
See 1 more Smart Citation
“…This implies that domestic firms are cheaper to acquire by foreign firms. Previous studies (Froot and Stein, 1991; Nisbet et al , 2003) with similar results indicated that strong currency lessens the costs of transaction, and therefore, firm that has its country’s currency depreciated tends to be a target. Although the countries of this ASEAN region made effort in maintaining strong currencies against the US dollars, their exchange rates depreciated substantially following the current plunge in crude oil prices.…”
Section: Resultsmentioning
confidence: 69%
“…However, Froot and Stein (1991) show that as strong currency lessens the costs of transaction and acquisition, firm that has its country’s currency appreciated tends to be an acquirer while the one that has its country’s currency depreciated tends to be a target. Therefore, when foreign currency depreciates relative to domestic currency, we should expect inward acquisitions and exchange rate to be negatively related and outward acquisitions and exchange rate to be positively related (Froot and Stein, 1991; Pablo, 2009; Nisbet et al , 2003).…”
Section: Theoretical Frameworkmentioning
confidence: 99%
“…They have been responsible for building a sound value configuration and for knowledge transfer to the local firms (Saliola and Zanfei, 2009). Such knowledge helps the local firms use various market entry strategies (Nisbet et al , 2003; Narula and Zanfei, 2003) and enhances their participation in the GVC. Even in cases of LDCs, participation of a small local firm in the value chains helps in obtaining information about products, technologies and for gaining market access (Pietrobelli and Rabellotti, 2011).…”
Section: Enablers Of Participation In Global Value Chainmentioning
confidence: 99%
“…Many studies of global value chains introduce new insights into the analysis of MNC organization and the increasingly complex ways they link with foreign counterparts. The changing nature of multinationals appears in the development of complementarities between internal networks of subsidiaries and external networks of cooperation with local firms and institutions (Castellani and Zanfei, 2004) and in the choice of alternative governance models for controlling activities including contractual agreements with local counterparts (Giuliani et al , 2005; Nisbet et al , 2003). Many authors (Gereffi et al , 2005) focus on opportunities for local producers to learn from global leaders who upgrade their products and processes and on how the enhancement of suppliers' capabilities allows leading firms to progressively outsource their activities.…”
Section: Mnc and Localization Strategymentioning
confidence: 99%